2006
DOI: 10.1002/bdra.20302
|View full text |Cite
|
Sign up to set email alerts
|

Wnt9b is the mutated gene involved in multifactorial nonsyndromic cleft lip with or without cleft palate in A/WySn mice, as confirmed by a genetic complementation test

Abstract: The noncomplementation of clf1 and Wnt9b- confirms that clf1 is a mutation of the Wnt9b gene. The homologous human WNT9B gene and 3' conserved noncoding region should be examined for a role in human nonsyndromic CLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
127
1
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(138 citation statements)
references
References 22 publications
(36 reference statements)
7
127
1
3
Order By: Relevance
“…Several reports discuss changes in Wnt family member gene expression in association with cleft palate, but only recently was loss of Wnt9b purported to be causal in the etiology of cleft palate in a mouse model (14). In this report, the authors confirmed that the previously described mutation clf1 in A/WySn mice was a mutation of the Wnt9b gene by a standard genetic test of allelism.…”
Section: Cleft Palatesupporting
confidence: 64%
“…Several reports discuss changes in Wnt family member gene expression in association with cleft palate, but only recently was loss of Wnt9b purported to be causal in the etiology of cleft palate in a mouse model (14). In this report, the authors confirmed that the previously described mutation clf1 in A/WySn mice was a mutation of the Wnt9b gene by a standard genetic test of allelism.…”
Section: Cleft Palatesupporting
confidence: 64%
“…In humans, mutations in the WNT3 gene are associated with tetraamelia and cleft lip and palate (Niemann et al, 2004). The A/WySn strain of mice exhibits an increased incidence of cleft lip and palate, and recent data indicate that this increased incidence can be exacerbated still further by deleting Wnt9b (Juriloff et al, 2006). Here, our data indicate a novel role for Wnt signaling in regulating species-specific craniofacial morphogenesis.…”
Section: Craniofacial Growth Is Influenced By Wnt Signalingmentioning
confidence: 51%
“…The mice were genotyped according to published protocols, except for the Pu⌬TK selector mouse line, for which we developed the following genotyping primers (from 5Ј to 3Ј): Hprtexon3rev, CTTACACAG-TAGCTC TTCAGTCTG; Hprtexon3for, TTTCTATAGGACTGAAAGACTTGC; and PgkNeoPromRev, GTGCTACTTC-CATTTGTCACGTCC, which yield a WT band of 187 bp, and a target band of 402 bp. Since the Pu⌬TK transgene is X-linked we also genotyped embryos for sex according to published protocols (Juriloff et al, 2006).…”
Section: Experimental Procedures Transgenic Mouse Lines and Genotypingmentioning
confidence: 99%